Organizational Design and the Intensity of Rivalry - Vroom, Govert (Management Science, 2006)
We analyze the effect of managerial compensation schemes and organizational structure on competitive behavior in imperfectly competitive product markets. Previous research suggests that in cases of strategic substitutability, firms tend to choose organizational structures and compensation systems that commit the firm to behaving aggressively in the product market, reducing firm and industry profits. In contrast, we show that while compensation and structure in isolation lead to excessive aggressiveness, the combination of these two internal choice variables may reverse the outcome—organizational design can be used as a commitment device to reduce competitive rivalry. Finally, we find that in equilibrium, firms may choose to be different; one firm is decentralized and uses incentives that commit it to being aggressive, while the other is centralized and uses incentives that commit it to being soft. Hence, endogenous firm heterogeneity in the form of organizational differentiation allows firms to avoid a mutually detrimental outcome.